Fractal Pattern of Particle Crushing of Granular Geomaterials during One-Dimensional Compression - Jiru Zhang; Biwen Zhang (Advances in Civil Engineering)
This paper focuses on the effect of particle crushing on the behavior of granular geomaterials. Series of high-pressure one-dimensional compression tests were carried out on a quartz sand-gravel. A detail investigation was performed primarily on the compression behavior, the evolution of particle-size distribution (PSD), the fractal pattern of the grading curve, and the amount of particle crushing. It was found that both the yielding state and the state at the maximum compressibility are closely associated with the evolution of PSD and the fractal pattern of particle crushing. As the vertical stress increases, the fractal characteristic of the grading curve appears only within the finer part at first, evolves into bifractal within the overall measurable grading curve late, and translates into monofractal finally. Furthermore, a pair of particle crushing indexes Be1 and Be2 considering different particle size scales were proposed. The reasonability of using Be1 and Be2 to describe the amount of crushing corresponding to the scale of particles was discussed. Finally, it was found that the value of the ratio between the volumetric strain and the crushing index Be1 is constant and independent of the initial particle size and the initial PSD when the vertical stress is larger than the stress at the maximum compressibility or the coarser part of the grading curve is evolved into fractal.